51. Tele-elettroencephalography to diagnose and treat epilepsy in a rural hospital in the south of Madagascar. Issue 12 (December 2017) - Morelli, M.E.; Padovani, M.; Pasotto, A.; Boarini, E.; Manganotti, P.; Monti, F.
Abstract : Epilepsy has a prevalence almost three times higher in Madagascar than in developed countries, and ninenty-two percent of people are not treated, because of health care and socio-cultural challenges. Perinatal damage, infections (malaria, neurocysticercosis) and trauma are among the most frequent etiologies. To improve care of epileptic patients referred to the "Vezo" Hospital, a tele-elettroencephalographic system was set up. From 2017, two health care professionals, working at "Vezo" Hospital, have been trained to record 13 electrodes-electroencephalograms (EEG), of 256 bytes and 10 min, using the EEG "EB Neuro" system, also used in our Unit. EEG are sent by email to our Unit in ".dat" and ".gnt" file extensions. From 2015, 132 epileptic patients have been visited and 28 EEG have been recorded. Of all patients, at onset of epilepsy, 51% were 20 years old or less, 14% had focal seizure, 7% had generalized epileptic abnormalities, 89% had still not EEG record, 6% had an etiological diagnosis of infection, 3% of head trauma, 83% had unknown etiology. Epileptogenic foci, possibly corresponding to infectious or traumatic sites, can frequently be at the origin of disease. Tele-elettroencephalography improves diagnosis and treatment possibility in rural areas, but more accuracy is required to define etiology.